The role of peer interaction in fostering student motivation in mathematics education - Amima Wulandari; Betty Kusumaningrum; Istiqomah Istiqomah; Tri Astuti Arigiyati; Luc Bergman (Universitas Sarjanawiyata Tamansiswa, 2025)
Mathematics is often seen as a challenging subject that demands not only cognitive ability but also sustained motivation. This study investigates how peer interaction can act as a catalyst for enhancing students’ motivation to learn mathematics. Adopting a qualitative approach with a survey design, data were collected from 40 high school and vocational students in Gunungkidul, Indonesia. Thematic analysis of open-ended questionnaire responses revealed that 72% of students reported higher motivation when learning alongside peers. Key motivational drivers included emotional support, collaborative problem-solving, and peer-driven encouragement. Interestingly, the study also highlighted potential setbacks such as interpersonal conflicts, which may reduce motivation. These findings affirm the transformative role of peer relationships in academic contexts and suggest that fostering supportive peer networks can be a strategic tool in improving students’ engagement with mathematics. This study contributes to educational psychology and mathematics education by demonstrating that peer interaction not only fosters emotional well-being but also improves students’ cognitive engagement with complex mathematical concepts. The findings offer practical insights into how structured peer collaboration can be integrated into instructional design to support diverse learner needs. By highlighting the dual role of peer interaction, as both an academic and affective resource, the study provides a foundation for developing socially responsive and student-centered learning environments aimed at improving mathematical achievement.